RAAIS: Rapid Appraisal of Agricultural Innovation Systems (Part I); a diagnostic tool for integrated analysis of complex problems and innovation capacity - Schut, Marc; Klerkx, Laurens; Rodenburg, J.; Kayeke, J.; Hinnou, L.C.; Raboanarielina, C.M.; Adegbola, Patrice Ygue; Ast, A. van; Bastiaans, L. (Elsevier, 2015)
This paper introduces Rapid Appraisal of Agricultural Innovation Systems (RAAIS). RAAIS is a diagnostic tool that can guide the analysis of complex agricultural problems and innovation capacity of the agricultural system in which the complex agricultural problem is embedded. RAAIS focuses on the integrated analysis of different dimensions of problems (e.g. biophysical, technological, socio-cultural, economic, institutional and political), interactions across different levels (e.g. national, regional, local), and the constraints and interests of different stakeholder groups (farmers, government, researchers, etc.). Innovation capacity in the agricultural system is studied by analysing (1) constraints within the institutional, sectoral and technological subsystems of the agricultural system, and (2) the existence and performance of the agricultural innovation support system. RAAIS combines multiple qualitative and quantitative methods, and insider (stakeholders) and outsider (researchers) analyses which allow for critical triangulation and validation of the gathered data. Such an analysis can provide specific entry points for innovations to address the complex agricultural problem under study, and generic entry points for innovation related to strengthening the innovation capacity of agricultural system and the functioning of the agricultural innovation support system. The application of RAAIS to analyse parasitic weed problems in the rice sector, conducted in Tanzania and Benin, demonstrates the potential of the diagnostic tool and provides recommendations for its further development and use.